An International Health/Medical Informatics Programs Database - Ball, M. J.; Protti, D. J.; Douglas, J. V. (Methods of Information in Medicine, 1994)
The University of Maryland at Baltimore has established a database of health/medical informatics programs worldwide. Since 1991, IMIA’s Working Group on Education and Training in Medical Informatics has provided guidance on critical issues of policy and purpose. At the Heidel-berg/Heilbronn Working Conference in 1992 on Health/Medical Informatics education, representatives to WG1 and participants made suggestions regarding database intent, structure, and attributes.
Keywords: Educational Programs; Medical Informatics; Nursing Informatics; Health Informatics